Conjugate rotor-stator interaction procedure for film-cooled turbine sections. Issue 3 (2nd May 2017) - Gottlieb, Joshua; Davis, Roger; Clark, John
Abstract : Purpose: The authors aim to present a procedure for the parallel, steady and unsteady conjugate, Navier–Stokes/heat-conduction rotor-stator interaction analysis of multi-blade-row, film-cooled, turbine airfoil sections. A new grid generation procedure for multiple blade-row configurations, including walls, thermal barrier coatings, plenums, and cooling tubes, is discussed. Design/methodology/approach: Steady, multi-blade-row interaction effects on the flow and wall thermal fields are predicted using a Reynolds's-averaged Navier–Stokes (RANS) simulation in conjunction with an inter-blade-row mixing plane. Unsteady, aero-thermal interaction solutions are determined using time-accurate sliding grids between the stator and rotor with an unsteady RANS model. Non-reflecting boundary condition treatments are utilized in both steady and unsteady approaches at all inlet, exit and inter-blade-row boundaries. Parallelization techniques are also discussed. Findings: The procedures developed in this research are compared against experimental data from the Air Force Research Laboratory's turbine research facility. Practical implications: The software presented in this paper is useful as both the design and analysis tool for fluid system and turbomachinery engineers. Originality/value: This research presents a novel approach for the simultaneous solution of fluid flow and heat transfer in film-cooled rotating turbine sections. The software developed in this research is validated against experimental results for 2D flow, and the methods discussed are extendable to 3D.